Cross-impact of leverage and firm performance: developed vs frontier bank-based economies. Issue 8 (12th August 2019) - Mishra, Sibanjan; Dasgupta, Ranjan
Abstract : Purpose: The purpose of this paper is to investigate the cross-impact of leverage and performance for firms operating in the developed and frontier bank-based economies. Design/methodology/approach: This study uses annual panel data for a sample of 400 firms over a period of 27 years from 1990 to 2016. The sample sample firms consist of developed, Germany, France and Japan, and frontier including Argentina and Sri Lanka bank-based economies firms. The authors employ a simultaneous equation modeling consisting of two equations estimated using the two-stage least squares procedure to examine the cross-relationships between leverage and performance after controlling for other firm-level variables like size, growth and liquidity. Findings: The empirical results are presented in two sets. First, in the case of firms in the developed bank-based sample, the authors find a negative debt-to-performance relationship and a negative performance-to-debt relationship. This inconsistent negative debt–performance relationship implies that firms operating in these economies use debt beyond a threshold limit, which, in turn, increases agency issues between the managers and debt-holders, thereby influencing firm performance adversely. Second, for frontier economies firms, the authors find a positive debt-to-performance relationship in line with the "trade-off theory." Furthermore, the authors find a negative performance-to-debt relationship for both sub-samples in line with the "pecking-order theory." Originality/value: The study is distinct from earlier empirical studies and contributes largely to the existing literature. First, it emphasizes whether financial leverage influences firm performance in bank-based economies as firms operating in such systems are exposed directly to the strict regulatory environment. Second, it investigates whether any reverse relationship emanating from firm performance to capital structure holds for firms of these countries. This issue, to the best of author knowledge, is unanswered in previous research, more specifically for developed and frontier bank-based economies. Moreover, the results are relevant, as firm managers, analysts and policymakers must consider the importance of such cross-debt-performance relationships, while determining the optimal capital structure, in the bank-based economies.